ANALISIS KOMPARATIF PENDAPATAN ANGGOTA KELOMPOK DAN BUKAN ANGGOTA KELOMPOK TANI PADI SAWAH SEMI IRIGASI DI DESA UJANMAS KECAMATAN PENGANDONAN KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
This study is to analyze the Comparative Revenue of Group Members and Non-Farmers Group of Rice Fields of Semi-technical Irrigation Farm in Ujanmas Village, District of Ogan Komering Ulu Regency with the objective to know how much income obtained by members and not members of Tani Semi-irrigated Rice Farmer Group in Ujanmas Village Kecamatan Pengandonan Kabupaten Ogan Komering Ulu. As well as to know the income ratio of members of the Tani Padi group and not the Rice Farmer group in Ujanmas Village District Pengandonan Ogan Komering Ulu Regency. Based on the research results obtained that the income earned by farmer group members amounted to Rp. 19,157,342 larger when compared with non-farmer's income of semi-technical irrigated paddy farmer group that is equal to Rp. 11,263,552 in Ujanmas Village District of Ogan Komering Ulu District. There is a difference in the income of the group members and not the members of the semi-technical irrigated rice paddy farmer group in Ujanmas Village District Pengandonan Kabupaten Ogan Komering Ulu. The income difference of farmer group members and non-farmer group members is Rp. 7,893,790.